Development of Technical Arrangement Skills and Food Serving Learning Using Digital Literacy Implementation Strategy - Darojatun, Anti; Febriana, Rina; Muksin, Muksin (UNIVERSITAS PAKUAN, 2023)
This study’s aim is to discover the implementation strategy of digital literacy in developing technical skills in food arrangement and presentation (food plating) among the students of SMKN 7 Tanggerang. This study uses a study case. In addition, this study uses a qualitative research approach; the technique of collecting data uses observation and in-depth interviews the qualitative analysis used interactive analysis model. the research Informants are the head of SMKN as a policy maker and 2 culinary teachers at SMKN 7 Tangerang City as executors of the digital literacy implementation policy. Data collection techniques in this study used observation techniques and in-depth interviews. The findings of this study convey that digital literacy helps students and teachers of the Culinary Arts Department of SMKN 7 Kota Tangerang in technical aspects of food arrangement and presentation (food plating. By applying digital literacy, students are better able to access instructions and materials because they only need to use their gadgets. YouTube is assessed to be the most used platform because it is easy to use and can send many files in a short time. Apart from using the YouTube platform, most students use other platforms. The platforms used are Google Classroom dan Pinterest.